The Effect of Color Light and Stocking Density on Some of External and Internal Egg Traits of Layers - Tabeekh , Mudhar A.S. Abu (International Journal of Poultry Science, 2015)
The study was conducted in the poultry farm of Veterinary Medicine College-University of Basra. This study was designated to investigate the effect of color light and stocking density on some productive performance of layers including external and internal characteristics of produced eggs. A total of 180 Isa Brown layers were used in this study with an average of 36 birds in each of five separated treatments were exposed to white light (WL) as a control, red light (RL), blue light (BL), green light (GL) and Blue-Green mix light (BGL) by a light-emitting diode system (LED) applied according to light intermittent program (16 h light-8 h dark) for 12 weeks with light intensity 5 watt/m2. In each treatment birds were randomly housed into 6 wooden sealed pens of 1 m2 in three replicates for each density 5 and 7 birds/m2. The results of the present study recorded significant interactions on accumulative egg production (Hen House) HH%, egg weight and egg mass in layers reared under RL at level of density 5 birds/m2. The results also revealed that light color and stocking density had no effect on egg shell weight, thickness, shell percentage, yolk weight, yolk ratio and albumin weight and ratio.